Integrating autonomy in public health messaging - Murphy, Katelyn; Graham, Devin; Faries, Mark (Frontiers in Communication, 2024)
The COVID-19 pandemic and related rise of public distrust has called personal autonomy in health messaging into question, drawing attention to two competing forms of health messaging -communicating to persuade versus to inform. Communicating to persuade utilizes marketing techniques to promote behavior change whereas communicating to inform focuses on providing information to facilitate informed decision-making. Communicating to inform is supported by Self-Determination Theory (SDT), which posits that autonomy, coupled with competence and relatedness, is a basic psychological need, relevant to making health-decisions and maintaining behavior change. This study aims to assess the above mentioned dynamics of SDT in health messaging through the development of an autonomous scale and assessment criteria. The purpose of the scale is to guide the development of health messaging that aims to communicate to inform (autonomy-enhancing) rather than communicating to persuade or coerce the audience into adopting a specific health behavior (autonomy-diminishing). The results of the study suggest that individual perception of autonomy in health messaging is influenced by a variety of factors.As such, the criteria outlined in this scale can be used as a guide to develop health messaging that purposefully integrates and supports autonomy-enhancing principles.